2012
DOI: 10.3399/bjgp12x641483
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of GPs' views and use of the fit note: a qualitative study in primary care

Abstract: BackgroundSickness certification constitutes daily clinical practice for GPs. In April 2010, the UK sickness certification system changed to reflect the evidence that work is generally good for health and a new Statement of Fitness for Work -the 'fit note' -was introduced. Sickness certification is a contentious topic among GPs and the proposed fit note generated mixed reviews. AimTo explore GPs' views and use of the fit note during its first year of operation. Design and settingQualitative interview study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Telephone interviews have been described as inferior to face-to-face interviews, for fostering rapport and recognising subtleties of communication [ 47 ]. However, they can also help interviewees feel comfortable when talking about sensitive topics within a medical context [ 48 ]. In our study the latter was relevant, since participants opened up about extremely sensitive events.…”
Section: Discussionmentioning
confidence: 99%
“…Telephone interviews have been described as inferior to face-to-face interviews, for fostering rapport and recognising subtleties of communication [ 47 ]. However, they can also help interviewees feel comfortable when talking about sensitive topics within a medical context [ 48 ]. In our study the latter was relevant, since participants opened up about extremely sensitive events.…”
Section: Discussionmentioning
confidence: 99%
“…To try and overcome some of these barriers, the UK Government encouraged GPs to issue injured workers with ‘fit notes’ rather than ‘sick notes’ to emphasise what people can do in the workplace and, thereby, facilitating labour market retention [ 7 ]. Several studies have since shown that there is recognition among UK GPs about the health benefits of work and that the fit note functions as a prompt to facilitate conversations around an earlier return to work [ 36 – 38 ]. The fit note also enables discussion between employees, employers, and GPs about appropriate, timely RTW and reduced sickness absence, which has wider benefits to injured workers, employers, and the economy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a system has been recently introduced in the UK, focusing on patients' ability rather than disability [9]. The introduction of a regulated self-certification system for short-term illness in Ireland may reduce the burden on GPs and create greater patient autonomy.…”
Section: Discussionmentioning
confidence: 99%